Teaching Through Interactions in Secondary School Classrooms: Revisiting the Factor Structure and Practical Application of the Classroom Assessment Scoring System–Secondary - Hafen, Christopher A. (J Early Adolesc, 2014)
Valid measurement of how students’ experiences in secondary school classrooms lead to gains in learning requires a developmental approach to conceptualizing classroom processes. This article presents a potentially useful theoretical model, the Teaching Through Interactions framework, which posits teacher-student interactions as a central driver for student learning and that teacher-student interactions can be organized into three major domains. Results from 1,482 classrooms provide evidence for distinct emotional, organizational, and instructional domains of teacher-student interaction. It also appears that a three-factor structure is a better fit to observational data than alternative one- and two-domain models of teacher-student classroom interactions, and that the three-domain structure is generalizable from 6th through 12th grade. Implications for practitioners, stakeholders, and researchers are discussed.